2017
DOI: 10.1111/ijfs.13573
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols, ascorbic acid and antioxidant capacity of commercial nutritional drinks, fruit juices, smoothies and teas

Abstract: SummaryPolyphenols of plant origin have received special interest in the last decade because of their potential health benefits. Consequently, many beverages with words 'antioxidant' and 'polyphenols' have been developed. However, many of the claims are misleading because some beverages so labelled have either no or minimal levels of polyphenols. The objectives of this study were to quantify polyphenols (TPC) and ascorbic acid contents and antioxidant capacity (AOC) of different beverages; identify major polyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 39 publications
(57 reference statements)
6
32
3
Order By: Relevance
“…Antioxidant foods and beverages have become increasingly popular because of their potential health benefits, which are attributed mostly to their bioactive compounds (Abountiolas and Nascimento Nunes, 2018). No standardized method has been established to determine the antioxidative abilities of food and beverages; therefore, the application of two or more methods is recommended to determine the antioxidative levels in a sample.…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidant foods and beverages have become increasingly popular because of their potential health benefits, which are attributed mostly to their bioactive compounds (Abountiolas and Nascimento Nunes, 2018). No standardized method has been established to determine the antioxidative abilities of food and beverages; therefore, the application of two or more methods is recommended to determine the antioxidative levels in a sample.…”
Section: Resultsmentioning
confidence: 99%
“…Among pomegranate juice based drinks, samples 2F (27.5%) and 2D (50%) from organic agricultural practices contained 10.4 and 26.1 mmol gallic acid/L, respectively. Whereas Abountiolas and Nascimento Nunes () reported in similar studies lower quantities of TPC for organic nectars with Pom (from 8.82 to 10.87 mmol gallic acid/L). TPC content in commercial Pom products is highly variable and cannot be related to farming practices.…”
Section: Resultsmentioning
confidence: 68%
“…It has been noticed that pomegranate juice based drinks including juices of grape, blackberry, raspberry, redcurrant, blackcurrant, chokeberry, and elderberry presented high values of CD, for instance 2P (5.27), 2L (3.81), 2D (3.38), and 2M (3.08). Abountiolas and Nascimento Nunes () reported that anthocyanins constitute a significant part of the pool of polyphenolic compounds of berries; hence, there was a direct influence of the addition of anthocyanin‐rich fruits on the CD values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent example is given by the paper by Abountiolas and do Nascimento Nunes (), which studied the antioxidant properties of 56 types of beverages available on the market: a significant positive correlation between total polyphenol content and antioxidant properties in fruit juices was found. Another current example is the study of Nowak, Gośliński, Przygoński, and Wojtowicz (), which showed as valuable source of antioxidants juice from exotic acai, noni, and maqui berry fruits.…”
Section: Antioxidant Properties Of Fruit‐based Juice: An Overviewmentioning
confidence: 99%